State, Development and Inequality in Selected ASEAN Countries: Internal and External Pressures and State Responses - Abdul Rahman Embong (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2015)
This article examines the role of the state in development, and the question of poverty, inequality and regional disparity in selected ASEAN countries Malaysia, Indonesia, Thailand and the Philippines in the context of both internal and external pressures faced by the state and how its responds to them. This article examines the historical context of the socioeconomic transformation, the current state of development, the high level of poverty in these countries (except Malaysia), the pervasive inequality and regional disparity, the various internal and external pressures exerted on the state and the latter's response to them. The article concludes by highlighting the importance of appropriate state policies for inclusive development and the role of civil society to exert pressure to ensure states perform such tasks. It argues that these issues are a result of state policies and institutional arrangements, and that to resolve them, appropriate inclusive policies need to be crafted and effectively implemented. The state has the autonomy and space to devise such policies but it is dependent on the political will of state actors and the role of civil society in engaging with the state to effect such reforms to address poverty, inequality and regional disparity effectively.
hdl:10398/9225
Keywords: 330; Southeast Asia; Poverty; Inequality; Regional disparity; State; Civil Society; Armut; Soziale Ungleichheit; Räumliche Verteilung; Sozialer Wandel; Entwicklung; Indonesien; Malaysia; Philippinen; Thailand